2019
DOI: 10.1038/s12276-019-0320-5
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 signaling regulates hematopoietic stem cell emergence

Abstract: Hematopoietic stem cells (HSCs) produce all lineages of mature blood cells for the lifetime of an organism. In vertebrates, HSCs derive from the transition of the hemogenic endothelium (HE) in the floor of the embryonic dorsal aorta. Most recently, a series of proinflammatory factors, such as tumor necrosis factor-α, interferon-γ, and Toll-like receptor 4, have been confirmed to play a key role in HSC specification. However, the full complement of necessary signaling inputs remains unknown to date. Here, we sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 63 publications
3
48
0
Order By: Relevance
“…Inflammation impacts crucial sites of erythrocyte production to redistribute resources toward myeloid cell production and therefore reduces lymphoid and erythroid output. For example, expression of pro-inflammatory IL-1β, interferon gamma (IFNγ), and IL-6 skew multipotential hematopoietic progenitors toward myeloid cell development ( Tie et al, 2019 ). This is an adaptive response since myeloid cells are needed to fight infection; however, this comes at the cost of bone marrow erythropoiesis.…”
Section: Pathophysiological Consequencesmentioning
confidence: 99%
“…Inflammation impacts crucial sites of erythrocyte production to redistribute resources toward myeloid cell production and therefore reduces lymphoid and erythroid output. For example, expression of pro-inflammatory IL-1β, interferon gamma (IFNγ), and IL-6 skew multipotential hematopoietic progenitors toward myeloid cell development ( Tie et al, 2019 ). This is an adaptive response since myeloid cells are needed to fight infection; however, this comes at the cost of bone marrow erythropoiesis.…”
Section: Pathophysiological Consequencesmentioning
confidence: 99%
“…In the context of inflammation, IL-6 induces emergency granulopoiesis, even in the absence of GM-CSF and G-CSF ( Ishihara and Hirano, 2002 ; Maeda et al, 2009 ). During zebrafish embryogenesis, IL-6 promoted the generation of hematopoietic cells and HSCs ( Tie et al, 2019 ). IL-6 has been used in some 2D-F protocols at the HP and MY stages ( Table 6 ).…”
Section: Exogenous Factors Used For Imph Differentiationmentioning
confidence: 99%
“…IL6 is a prominent proinflammatory cytokine that plays a critical role in modulating immunity and inflammation, 51 , 52 and also regulates the proliferation and differentiation of HSCs. 53 Interestingly, we found that H2R-agonist treatment reduced the level of IL6 in the circulation, spleen, and colon, and suppressed the activation of HSCs, leading to improved survival of mice with severe colitis. HSC differentiation is induced by the cytokine granulocyte-macrophage colony-stimulating factor (GM-CSF), which is thought to drive HSCs to differentiate into common myeloid progenitors.…”
Section: Discussionmentioning
confidence: 74%